The Use of Chemical Fertilizer Technology in Eastern Hills of Nepal: Knowledge, Attitude and Practice (KAP) - Wagle, Shyam Prasad (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
The use of new technologies issue in agricultural sector is the global concern of the current days. This paper attempts to assess about the knowledge, attitude and practice of farmers related to the use of chemical fertilizers in their agricultural works in the case of eastern hills of Nepal. The study applied household questionnaire survey, key informant survey, focus group discussion and field observation to collect relevant information. The study conducted in 30 percent (180hss) in total (601hhs) of three altitude belts such as upper, middle and lower, ranging from 300 to 2,250 masl along the Koshi-highway. It has a wide range of climates, ranging from sub-tropical to alpine with monsoon precipitation in the summer three and half months. Secondary data were gathered from previous research journals, dissertations and official records. This paper has showed that chemical fertilizer technology is well known technology for the protection and promotion of fruits, crops and vegetable in the study area. Around 79 percent (142hhs) farmers have used this as an useful and profitable technique. Despite various problems, the practice of this technology is gradually increasing in this area and the maximum practice is concentrated with vegetable farming. Although it was introduced through the inspiration of local research centers at first time, the role of neighbours, friends/ relatives and television programs seems to be significant respectively in its development and expansion in the study area. This technology is the choice of the farmers and also they have positive attitude towards it but the amount of adoption is declined through the negative impact of unscientific practice in the actual field.